(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
A trackless train is a rail-less train for urban passenger transport that can run across the road by using wheels, fuel, and batteries. It can carry a large number of passengers to their destinations and have its lane to avoid traffic unlike a bus or any vehicle that overtakes the road and can cause heavy traffic during rush hour. Therefore, the researchers developed a product that commuters can ride from Valenzuela to Guiguinto Bulacan without experiencing traffic jams and inconvenience. This study utilized the quantitative-experimental research design. The respondents of the study were five civil engineers and five mechanical engineers to test the significant differences in the level of acceptability of trackless train miniature in terms of construction materials, seating capacity, structural design, mechanism, and project design. In the construction of the miniature, the general procedures are as follows: provide the accurate measurements and dimensions of the trackless train miniature, make the vehicle plan as a guide for the construction, prepare and make sure that all the materials that will be used are durable and firm, prepare the cardboard and make the desired structure of the train, arrange the DC motors with its electrical and batteries, attach the DC motors in the structured cardboard train, make the road and platform of the train out of cardboard, attach the small bulbs for the ceiling of the miniature train stations, paint it with the roads and train, and design the small details on the stations to complete the miniature of the trackless train. The results of the study in terms of construction materials, seating capacity, structural design, mechanism, and project design were acceptable. Therefore, the difference between the assessments of the two groups of respondents is not significant. Civil engineers obtained an overall weighted mean of 2.70, which was interpreted as acceptable with a variance of 0.0141, a t-computed of 2.55, and a degree of freedom of 8 with the value of 2.896. The t-critical value was greater than the t-computed one. Therefore, the assessments of civil engineers are accepted. Meanwhile, mechanical engineers obtained an overall weighted mean of 2.97, which was interpreted as acceptable with a variance of 0.0419, a t-computed value of 2.55, and a degree of freedom of 8 with the value of 2.896. The t-critical value was greater than the t-computed one. Therefore, the assessments of mechanical engineers are Accepted. As a result, the assessment of two groups of respondents is accepted. The respondents recommended the following: use other light and hard materials instead of thin cardboard to improve the appearance of the station miniature; change and add more seats to fit the maximum person and to be presentable, make the trackless train miniature wide for better appearance inside the train with the use of stronger boards, allot more time to the mechanism of the train for better functioning and make use of lighter batteries and DC motor, be consistent and rely on the specific measurements, and add more details to the station for safety measures.